2023
DOI: 10.1177/15347346231172566
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Standard Compression Adjuvant with a Tailored Exercise Training Program on Health-Related Quality of Life Outcomes in Treating Adults with Venous Leg Ulcer: A Randomized Controlled Trial

Amaraporn Rerkasem,
Sothida Nantakool,
Kanokwan Kulprachakarn
et al.

Abstract: Exercise training adjuvant to standard compression is considered to improve calf muscle pump dysfunction in venous leg ulcer (VLU) and subsequent healing. The objectives of this trial were to assess the effectiveness of a tailored exercise training intervention in addition to standard compression therapy on health-related quality of life and anticipating wound healing. Twenty-four VLU participants were recruited and randomly divided into 2 groups. The control group was prescribed conventional compression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This review comprised 10 studies published between 2010 and 2023, 9 RCTs and one before‐after study. 23 A total of 2333 participants were included in the studies (mean: 233; SD: 243; min 24 36 ; max 675 26 ). The majority were conducted in the UK (44%; n = 4/9) or across multi‐geographical sites including the UK and other countries (22%; n = 2/9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review comprised 10 studies published between 2010 and 2023, 9 RCTs and one before‐after study. 23 A total of 2333 participants were included in the studies (mean: 233; SD: 243; min 24 36 ; max 675 26 ). The majority were conducted in the UK (44%; n = 4/9) or across multi‐geographical sites including the UK and other countries (22%; n = 2/9).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, Clark Maloney 29 reported no statistically significant difference in bodily pain between the study groups (Median (IQR): 4LBG: 84 (61–100); usual care: 72 (51–100); p = 0.840). Conversely, 3 studies found that pain was reduced in the intervention groups, Klonizakis, Tew 35 intervention group: 7.9 ± 22.8; control group: 30.5 ± 36.6; Berszakiewicz, Kasperczyk, 23 SF‐36: bodily pain, before compression: 0.00 (±0.00); after compression: 66.56 (±13.26), CIVIQ‐20: pain dimension: before compression: 19.73 (±0.69); after compression: 8.6 (±1.61), and Rerkasem, Nantakool 36 : intervention 92.9 (SE: 4.9); control: 89.1 (SE: 4.9) (see Table 4 ).…”
Section: Sf‐12mentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature posits that exercise training may exert positive effects on the treatment and management of VLUs 28 . This form of training encompasses diverse modalities such as aerobic exercise, resistance training, and flexibility training, as well as habitual daily activities like walking and housework.…”
Section: Discussionmentioning
confidence: 99%